Problem żydowski w Galicji u schyłku XIX i w początkach XX wieku w interpretacji zwolenników asymilacji i narodowych demokratów (do roku 1907) - Sobczak, Mieczysław (The Jewish issue in Galicia towards the close of the 19th century and at the beginning of the 20th century in the interpretation of adherents of assimilation and the national democracy (till the year 1907), 2007)
At the turn of the 19lh century, the national trend appeared among the Galician Jews which caused changes in behaviour especially among young generation. At the instance of Zionie ideology some Jews realized that they have a separate national identity. According to the spirit of the new ideology they created the Jewish policy. The Polish side was afraid that this situation could change the existing political system especially in the East Galicia. Both the adherents of assimilated solution of the Jewish issue and the ideologists of the Polish nationalism were afraid of the third nationality (besides Poles and Ukrainians). These two sides had a different conceptions of solving the Jewish issue.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 116-135